2000
DOI: 10.1177/030908920002508802
|View full text |Cite
|
Sign up to set email alerts
|

Vision and Voice in Isaiah

Abstract: This essay consists of four sections, interwoven with a dilatory commentary on the first few verses of Isaiah. They are concerned with the metaphors of vision and voice in Isaiah, as they relate to the problem of metaphoricity in general, and the ever-presence of death in the book. Vision and voice are metaphors for each other, and opposed terms. If vision suggests clarity and exteriority, voice evokes the interiority of the person, and an intimation beyond the horizon. Both terms are contradicted, and paradox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Other recent studies have found literary cohesiveness in Isaiah by reading it as a liturgy in eight acts (Goulder 2004b), or by tracing themes through large swaths of the book, such as sickness and health (Kustár 2002), light and darkness (Vlková 2004), speech and vision (Landy 2000b), the city (van Wieringen and van der Woude 2011), etc. Everson and Kim (2009) is a collection of literary studies on the book including a number by prominent scholars.…”
Section: Centripetal Approaches To Isaiah 1–66mentioning
confidence: 99%
“…Other recent studies have found literary cohesiveness in Isaiah by reading it as a liturgy in eight acts (Goulder 2004b), or by tracing themes through large swaths of the book, such as sickness and health (Kustár 2002), light and darkness (Vlková 2004), speech and vision (Landy 2000b), the city (van Wieringen and van der Woude 2011), etc. Everson and Kim (2009) is a collection of literary studies on the book including a number by prominent scholars.…”
Section: Centripetal Approaches To Isaiah 1–66mentioning
confidence: 99%
“…In a discussion of interpretive interests, Mark G. Brett (1990) has 2 I refer to places where the character speaks in the first person singular voice. In the "Abstract" of F. Landy's (2000) article on Isaiah, the author states that "if vision suggests clarity and exteriority, voice evokes the interiority of the person, and an intimation beyond the horizon" (p. 36). The same contradicted and paradoxical elements are found in Daniel 7-12, where both visions and the "I" voice of Daniel are present.…”
Section: Positioning My Approach In the Fieldmentioning
confidence: 99%
“…In a study devoted to vision and voice in Isaiah, Francis Landy (2000) has come to the conclusion that, "if vision suggests clarity and exteriority, voice evokes the interiority of the person and an intimation beyond the horizon" (p. 36). The same could be said of my "port of entry" here.…”
Section: The World Of the Textmentioning
confidence: 99%